Topographic-anatomical peculiarities of the larynx in fetal period of embryogenesis - Popelyuk O.-M.V. (Морфологія, 2009)
The dynamics of morphogenesis and syntopia of human larynx in connection with organization of adjacent structures was studied. The development and changes of topographic-anatomical correlation of larynx with adjacent structures was researched successively, the formation of its shape, structural organization, the influence of blood vessels and nerves on mentioned area was determined during the fetal period of human ontogenesis.